Preparing veterinarians to respond to animal victims: understanding and treating the behavioral consequences of maltreatment - Segurson, Sheila (Animals as crime victims, 2024)
Animals who experience maltreatment, such as physical abuse, starvation, social isolation, and environmental deprivation, may suffer long-term psychological effects and emotional harm. An animal’s likelihood of experiencing posttraumatic stress and long-term behavioral consequences is related to many factors including their relationship with people or other animals, past experiences, genetics, the degree and duration of stress involved with the incident, and their perception of the experience. Support for animals who have experienced maltreatment begins with assessing their behavior. Treatment of these animals should include creating a sense of safety, providing them with a sense of control, protecting them from exposure to stressful stimuli, and reducing negative and increasing positive experiences. Depending on the severity of the animals’ symptoms, treatment might also include behavior modification and medication. With appropriate treatment, monitoring and support, many animals who have experienced maltreatment can live long, happy, and healthy lives.